Технологія планування траєкторій руху мобільних об’єктів з урахуванням перешкод на складній місцевості - Ковалець, І. В.; Гунченко, Ю. О.; Комарчук, Д. С.; Лукін, В. Є. (Енергетика і автоматика, 2017)
TECHNOLOGY OF TRAJECTORY PLANNING OF MOBILE OBJECTS MOTION WITH REGISTRATION OF LIMITS IN DIFFICULT LOCATION I. V. Kovalets, Yu. A. Guntchenko, D. S. Komarchuk, V. E. Lukin One of the most promising areas of robotics is route planning or navigation of autonomous mobile robots (MR). The purpose of navigation MP is to find the optimal (according to given criteria) trails him move between given points based residential space (passive) and mobile (active) interference. Therefore, the development of new models, methods and algorithms for navigation of autonomous mobile robots to suit different types of barriers is relevant scientific and technical challenge.Analysis of recent research and publications show that is now widely used global and local methods of navigation MR. The disadvantages of global methods include the need to maintain maps (often large) and increased computational complexity. Local navigation methods used in those cases where MRI is not known, fixed (passive) and moving (active) interference that may come and go and spell your location. The advantages of local navigation methods include their computational simplicity. Disadvantages of these methods compared to global navigation methods consist of real trajectory deviation from the optimal route MR and more complicated procedure MRI localization in space. For both groups of methods of navigation MR typical problem of timely identification of passive and especially active obstacles to movement MR. In addition, existing methods and algorithms for solving problems of planning trajectories ground MRI used in two stages: the first is the global trajectory for map data, which is then periodically during movement utochnyayetsya according to the board of technical systems (TRS) MP. Such an approach inherent contradictions and flaws caused significant scale difference providing information on these two stages.The aim - to develop technology planning routes MY depending on the obstacles identified using temporary storage.The paper proposed a combined method of navigation MR, based on a combination of approaches, characteristic for both global and local methods for navigation. If there STZ based on the variant UAV trajectories planning MRI in three stages using map data (global trajectory), data warehousing based on UAV (tactical trajectory) and data warehousing LL (local path). Tactical trajectory, which is based on data from temporary storage at the UAV, is a closed path that passes through the terrain. The target point global plan provides for endpoint routing task MR, target points on a tactical level planning will be a sequence of points belonging global trajectory and target points on the local level are planning a sequence of points belonging trajectory, constructed at the tactical level planning. This area, which moves ll consists of two types of areas, open areas and obstacles that MRI can directly overcome. If the obstacle is on the way MP, he must overtake her.Modern information systems and technologies include a large number of procedures that support process modeling or predictive motion planning of mobile objects (MO). By this simple type is any classification of quantitative data on user-defined criteria, provide analysis of complex scenes, processes, events to plan routes IU difficult terrain.According to different expert input cost can reach 80% of the entire GIS project, including the cost of hardware costs. Errors and omissions made during data entry can lead to distortion of information in subsequent stages of processing and completely devalue the outcome. Therefore, before entering assessment data is the information system needs at all stages of its operation, selected data source arranged list of information objects, are formalized their detailed descriptions plan developed consecutive numbering. Obligatory element input is selective or complete control accuracy and completeness of the administration.In systems processing and analysis of remote sensing data range of treatments of this type are the most widespread. Almost all the thematic decryption process has staged picture group and subsequent transformation of data in order to create a completely defined, problem-oriented pattern areas of the earth's surface. Most of these steps is provided methods and algorithms within the specialized tool packages and the task handler is to create the most effective data classification scheme.The problem is solved by using a special information technology, which involves obtaining data on land area of unmanned aircraft in the optical and process photos using GIS. Photographing defined surface is made from a height of 1 to 250 m with the possibility of assistance in receiving